Traits of Sheep and Effects of Protein Supplements on Semen Profile in Indigenous Sheep of Bangladesh - Kabirul Islam Khan; Iqbal Hossain; Moksedul Momin; Gous Miah; Nurul Quader; Omar Faruk Miazi (Indonesian Center for Animal Research and Development (ICARD), 2019)
The study was carried out at Chittagong district of Bangladesh with a predesigned well-structured questionnaire to know the baseline information of indigenous sheep and effects of protein supplementations on fertility. Three iso-caloric but different graded levels of protein containing rations were supplied to the three different groups of sheep in three locations. The morphometric traits of sheep such as hair length, ear length, tail length, body length and quantitative trait, body weight in the location 3were higher than the other two locations. Hair length of male (1.91±0.01cm) was longer than female whereas the average body length, tail length and body weight of females were higher than the males. All the correlation values was positive, where the highest value was observed among the body weight, body length and withers height (r=0.73) and the lowest value was observed in between chest girth and ear length (r=0.25). Considering the qualitative traits percentage of plain coat color, non-pigmented skin color, brown coat color and semi-pendulous ear found maximum than others and the values were 54.21%, 69.16%, 45.79%, 57.01%, respectively. The semen volume, sperm counts, percentages of normal and viable sperm were higher in treatment 2 than the other two groups. The present study concluded that there is an influence of protein supplementation on reproductive performance especially semen profile in ram and this outcome will create a new horizon of sheep production in Bangladesh.